Economic Assessment of Sanitation Interventions in Lao People's Democratic Republic - World Bank (Washington, DC, 2014)
Access to improved sanitation is a major concern in the Lao People s Democratic Republic. Only 63 percent of the population of the country had access to improved sanitation facilities in 2010. Sanitation conditions are worse in rural areas. This study aims to generate evidence on the costs and benefits of sanitation improvements Lao PDR.